Urbanisation and rural-urban migration: evidence from Chongqing in the period 2001 to 2011 - Ou, Jinghua (2013)
Following the launch of the 'Develop the West' strategy in 2000, western China has undergone huge changes. Chongqing has been at the leading edge of this wave of development and its model of economic reform is particularly interesting and has also attracted public attention. This study aims to answer a series of unexplored questions about Chongqing's urbanisation and rural-urban migration. The first empirical chapter (Chapter 4) derives a simultaneous equation model from the standard theoretical framework of wage growth to estimate the determinants of wage growth of urban workers of various industries and the effects of openness. Data for 38 industries in Chongqing over the past 11 years is grouped into four sets of panel data in terms of different magnitudes of openness. The data shows that the increase in the demand for labourers is positively related to the wage' growth of urban workers. Openness, captured by industry's utilisation or non-utilisation of FDI, impels industrial sectors to use automation techniques more efficiently. The effect of productivity on wages in the group of industries which do utilise FDI is more than twice that of those in the group of industries which do not. Moreover, this chapter has not found enough empirical evidence to support the theory that the building of new cities benefits urban wage growth.